ANALISIS DAMPAK SOSIAL DAN DAMPAK EKONOMI KEBERADAAN KAMPUNG BATIK DI KELURAHAN BETUNGAN KOTA BENGKULU - Pitriani, Melisa; Heriyanti, Lesti (JURNAL ILMIAH IDEA, 2026)
This study aims to determine the social and economic impacts of the existence of batik villages in the Betungan Village, Bengkulu City. researchers used qualitative research methods, with a case study approach, research informants were determined through a purposive sampling technique (determination of the sample with certain considerations) research data was collected through data collection techniques namely observation, interviews, decomments and document collection. Then analyzed through the stages of data reduction, data presentation, and drawing conclusions. Analysis of the results of the research was analyzed using Robert K. Merton’s Structural-Functionalism Theory of manifest function Based on the research that has been done, the results of the research show that there is a manifast function and a latent function of the existence of the Betungan batik village towards artisans. The manifest functions are: increasing togetherness or solidarity in the community, increasing community expertise, preserving cultural arts, increasing family income, increasing family assets, improving housing conditions. These latent functions are: Reducing the interaction of togetherness in the family, increasing household expenses